Factors affecting perception and acceptance of colonoscopy in patients with inflammatory bowel disease - Chang-Hung Liao; Peng-Jen Chen; Yu-Lueng Shih; Wei-Kuo Chang; Tsai-Yuan Hsieh; Tien-Yu Huang (Preventive Medicine Reports)
Objective: The noncompliance rate with routine or surveillance colonoscopies is high, and the underlying reasons remain unverified among Asian patients with inflammatory bowel disease (IBD). This study aimed to examine the perceptions of Asian patients with IBD regarding bowel preparation and colonoscopy and their attitudes toward the recommended intervals for colonoscopies. Methods: Using data from one medical center between July 2020 and May 2022, we analyzed the perceptions of bowel preparation and colonoscopy and attitudes toward examination intervals among 94 patients with IBD (Crohn's disease, 41; ulcerative colitis, 53). The patients' perceptions of the four components associated with the colonoscopy procedure (embarrassment, pain, use of bowel-cleansing agents, and stress) were assessed via a questionnaire. Patients were asked to indicate the frequency at which they had scheduled colonoscopy and the frequency at which they desired to undergo the procedure. Results: “Bowel cleansing” and “pain” received the highest dissatisfaction rate. “Drink too much” was the greatest burden in bowel preparation. Younger age and younger age at diagnosis were associated with a greater burden of bowel preparation and pain. Younger patients and those diagnosed at an earlier age tended to prefer longer examination intervals. Conclusions: Bowel cleansing and abdominal pain were the most uncomfortable aspects associated with colonoscopy, especially when performed without sedation, among Asian patients with IBD. Younger patients and those with early diagnoses preferred longer examination intervals. Our findings can promote colonoscopy adherence and facilitate early detection of major complications in patients at high risk and those with long-term IBD.